2020
DOI: 10.1016/j.cllc.2019.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Agreement on Major Pathological Response in NSCLC Patients Receiving Neoadjuvant Chemotherapy

Abstract: The assessment of MPR was reproducible between observers. We confirmed that MPR is associated with OS and can serve as an independent prognostic factor in NSCLC patients undergoing neoadjuvant chemotherapy. Our data suggest that at least 3 slides should be read to accurately determine tumor response. Our results clearly demonstrate that MPR is a significant predictor of OS. Introduction: We have suggested that major pathologic response (MPR) could serve as a surrogate endpoint for survival and provide rapid me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 17 publications
3
70
1
Order By: Relevance
“…Further comparison of the postoperative pathological remission of the two groups showed that the immunotherapy group had a higher MPR. Some research suggests that the MPR may be related to the long-term survival of patients and that it will become an indicator of the survival time of patients in the future, but more research is required to confirm this (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Further comparison of the postoperative pathological remission of the two groups showed that the immunotherapy group had a higher MPR. Some research suggests that the MPR may be related to the long-term survival of patients and that it will become an indicator of the survival time of patients in the future, but more research is required to confirm this (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…So, the 5-year survival rate of patients is very low 8 . The current surgical treatment, chemotherapy and other means can't signi cantly improve the survival rate of patients, but greatly reduce the quality of life of patients at the same time 9 . It brings heavy economic burden to the patients' families, which makes countless families fragmented.…”
Section: Discussionmentioning
confidence: 99%
“…Although pCR after neoadjuvant therapy may be an effective alternative measurement for OS [77, 78], pCR is rarely used as the primary endpoint in clinical trials [52, 53]. MPR, defined as ≤10% of viable tumor cells in a surgically resected specimen, is more commonly used in clinical trials because it has a higher incidence than pCR [79]. Many studies have reported that MPR is predictive of the OS of patients with early‐stage NSCLC [77, 80, 81].…”
Section: Challenges and Unanswered Questionsmentioning
confidence: 99%